Let's have a play - Hillert, Margaret; Elzaurdia, Sharon (Parsippany, NJ : Modern Curriculum, 1981)
On a rainy day, two children decide to make paper-bag puppets and put on a play for themselves and their parents.
School Library Journal
Horn Book
1.2
K-3
Keywords: Puppets and puppet plays -- Fiction